Hetero‐Tetranuclear Cu2+/Ca2+/Ca2+/Cu2+ Architectures Based On Malten Ligand: Scaffold for Anion Binding. Issue 6 (4th June 2020) - Rossi, Patrizia; Macedi, Eleonora; Formica, Mauro; Giorgi, Luca; Paoli, Paola; Fusi, Vieri
Abstract: The hetero‐tetranuclear Cu 2+ /Ca 2+ /Ca 2+ /Cu 2+ complex obtained with the N, N'‐bis((3‐hydroxy‐4‐pyron‐2‐yl)methyl)‐N, N'‐dimethylethylendiamine (Malten) ligand has been studied in solid and solution states as scaffold to bind anions. Three crystal structures showing the same metal ions sequence have been examined; they display a tetracharged complex cation neutralized by four monocharged anions. The anions play two different roles: as coordinated (two ClO4 −, Cl − or NO3 − ) or ancillary (two ClO4 − ) guests. The tetranuclear scaffold hosts two anions also in aqueous and ethanol solutions. Spectrophotometric studies in ethanol allowed to determine the addition constant values for Cl − and Br − (Log K 1‐2 =4.43(4), 4.39(3) for Cl −, 3.80(3), 3.54(2) for Br − ) while the others, although bound, showed lower affinity for the scaffold. Both the crystals and the solutions change their color depending on the added anion, namely pink, dark green or blue in the presence of ClO4 −, Cl − or NO3 −, respectively, thus the presence of the different anions is visible to the naked eye. The hetero‐tetranuclear Cu 2+ /Ca 2+ /Ca 2+ /Cu 2+ complex is a versatile architecture to be used as scaffold for anion binding. Abstract : Tetranuclear anion host : The hetero‐tetranuclear Cu 2+ /Ca 2+ /Ca 2+ /Cu 2+ complex results a versatile architecture for anion binding. It can host two monocharged anions, as those of the halide series, ClO4 − and NO3 −, which are coordinated to the metal sequence. The hosted anion affects the system giving different colors to both crystals and solutions, so that its presence can be seen by the naked eye.